Perlindungan Hukum Pengelolaan Hak Atas Tanah Yang Bersertifikat Terkait Perubahan Peruntukan Menjadi Konservasi Kehutanan - Sri Mulyani; Joko Sriwidodo; Basuki Basuki; Yuhelson Yuhelson (Magister Pendidikan Nonformal Pascasarjana Universitas Negeri Gorontalo, 2023)
This article discusses the legal protection of the management of land rights that are certified related to the change in designation to forestry conservation. This is a problem because the status of the certificate of land rights whose designation has changed to forestry conservation. How to analyze and understand the legal consequences and know the legal protection of the management of certificated land rights that are included in forestry conservation. The research method used by researchers is normative juridical. In this study, the issues to be discussed are the legal consequences of managing certified land rights related to the change in designation to forestry conservation and legal protection for the management of certified land rights that are included in forestry conservation. The theory of legal consequences used is Soeroso's theory and its legal protection uses Philipus M. Hadjon's theory. The result of this research is that the legal position of certificates of land rights is as a means of proof for the holders of their rights and to guarantee legal certainty in society. Land rights certificates have strong evidentiary characteristics, as long as there is no other evidance to prove otherwise.